INOVASI PRODUK HALAL SPINDA ICE CREAM BERBASIS BAYAM DAN EDAMAME: UJI ORGANOLEPTIK DAN KARAKTERISTIK FISIK - Yati Nurhayati; Yuny Ernawati; Neneng Windayani; Ateng Supriyatna (Universitas Mathla’ul Anwar Banten, 2026)
Innovation in halal plant-based food products continues to grow along with increasing public awareness of healthy and functional foods. This study aimed to evaluate consumer acceptability and physical characteristics of Spinda Ice Cream, a spinach- and edamame-based ice cream developed as a halal plant-based product innovation. The research employed a Completely Randomized Design (CRD) with one treatment factor, namely variations in spinach proportion, consisting of three formulations: F1 (low), F2 (medium), and F3 (high). Organoleptic evaluation was conducted using a 1–7 hedonic scale involving 30 untrained panelists, assessing color, aroma, texture, taste, and overall acceptability. Physical analyses included density, pH, and melting properties. Organoleptic data were analyzed using the Kruskal–Wallis test, followed by the Mann–Whitney test for parameters showing significant differences. The results indicated that all formulations were acceptable, with F2 consistently receiving the highest preference scores across all sensory indicators. Aroma was the only attribute showing a significant difference among formulations. Physical testing showed that F2 exhibited the most balanced characteristics. From a Halal Science perspective, Spinda Ice Cream fulfills the principles of halalan thayyiban and has strong potential to be developed as an innovative halal plant-based ice cream product.